Slovak Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix examines external competitiveness and the exchange rate for the Slovak Republic. The paper describes two simple types of competitiveness indicators: (i) real effective exchange rate measures, which examine underlying fundamentals thought to influence external performance; and (ii) indicators of actual export performance. The results suggest that the unfavorable outcomes in the merchandise trade balance and the current account from 1996 to 1998 reflected, at least in part, competitiveness problems. The paper also presents an assessment of banking conditions and the supervision system in the Slovak Republic.